Analisis Risiko Human Error dalam Penggunaan Microsoft Excel dan Dampaknya terhadap Kualitas Laporan Keuangan - Elis Oktaviani; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to develop a conceptual framework for analyzing the risk of human error in the use of Microsoft Excel and its implications for the quality of financial reporting. The research adopts a non-empirical qualitative approach using a descriptive-conceptual design based on a systematic synthesis of relevant literature in accounting information systems, internal control, and financial reporting quality. The analysis identifies that human error arises from the interaction between user limitations, system design deficiencies, and the absence of automated validation mechanisms within spreadsheet-based environments. These errors manifest in various operational forms and lead to significant distortions in the accuracy, reliability, and relevance of financial information. The study further highlights that reliance on Excel as a primary accounting tool increases exposure to risk due to its dependence on manual processes and individual competencies. The findings contribute to the theoretical development of risk management in accounting systems and offer practical implications for improving financial reporting quality through system transformation.